Communication—Phosphate K(Mo2PO6)(P2O7) as a Novel Cathode Material for Potassium Ion Batteries: Structure and Electrochemical Properties. Issue 11 (7th July 2020) - Dai, Siyi; Feng, Tingting; Chen, Cheng; Li, Xinran; Wu, Mengqiang
Abstract : A novel phosphate material K(Mo2 PO6 )(P2 O7 ) was successfully prepared by the high temperature solid-state method for the first time and applied as a cathode material for potassium ion batteries. The as-prepared K(Mo2 PO6 )(P2 O7 ) compound exhibited a stable reversibility of K + intercalation/deintercalation, and delivered a capacity of 57 mAh·g −1 at a rate of 0.1C when cycling between 1.5 V and 4.1 V. The changes in the crystal structure and surface electronic states of elements during the charge-discharge of K(Mo2 PO6 )(P2 O7 ) electrode were studied. This work may develop a new promising cathode material for K-ion batteries.